A Preliminary Research on Combustion Characteristics of a Novel-Type Scramjet Combustor. (30th December 2022) - Zhang, Linqing; Chang, Juntao; Cai, Wenxiang; Sun, Hui; Li, Yingkun
Abstract : In this work, a new configuration of strut-based scramjet is proposed, and a series of simulations are conducted to investigate its possibility of practical application. The simulation results are verified via the classical DLR ramjet and an experiment conducted on the connected pipe facility. The inlet area (A in ) and air intake height (H ) of the combustor are varied independently to investigate their performance. The results indicate that the flow field and shock wave structure of such engine reveal similar characteristics as the classical DLR engine, and the variation in engine geometry can significantly affect its combustion characteristics. Moreover, the combustion efficiency could be enhanced by 2% as the A in varied from 900 π mm 2 to 1100 π mm 2 ; increasing the air intake path (H ) to 12 mm can increase the combustion efficiency by 25%. In general, the present work proposes a new geometry of the scramjet combustor; this combustor has possibility of practical application, but a further and detailed investigation is still needed.